Keandalan Bangunan Hunian Warga Terhadap Risiko Bencana di Kampung Batukasur Desa Batulayang Cisarua Bogor - Juwono, Sudarmawan; Ali, Abdullah; Mulyo, Yusak Sabdono; Laia, Alesman; Purba, Leonardo Fransisco (Jurnal Pengabdian Masyarakat Singa Podium (JPMSIPO), 2023)
The reliability of a building, as regulated by law, is an indicator of its ability to provide safety for its occupants. In order to map the potential risks of residential buildings, a survey was conducted to assess the reliability of 94 residential units in the Batukasur village, Batulayang village, Cisarua district, based on building reliability criteria. This location was chosen due to its hilly geographic conditions and the fact that the houses were self-built by residents. The method used was a questionnaire, which was used by students to observe and interview residents to obtain information describing the level of building reliability. The results of the observation showed that the reliability level of the residential buildings reached 3.66, which is between poor and good. The lowest value was the accessibility level, which reached 3.48, while the highest was health, with a value of 3.88 on a scale of 1 to 5. These conditions indicate that the residential conditions are relatively good, but the low accessibility level should be noted, as it can limit mobility during the evacuation process. This condition is closely related to the level of resident participation and knowledge of disasters. Furthermore, the mapping results can be used as information for the village regarding the level of building reliability.